Case study of construction disputes on SOP act - Huang, Shuzong (2016)
Construction projects are usually large scale projects that involve a lot of money. It is very important for companies to make payments promptly so as to ensure the smooth cash flow between main contractors and sub-contractors. Traditionally, companies with payment disputes will go through a long and costly process before reaching a conclusion because the legal firms handling such cases were usually not well equipped with the knowledge on construction industry. Companies, especially small firms, find it very inefficient to find mediator to solve such payment disputes. As a result, they may face cash flow problems which may result in bankruptcy. The enactment of the Security of Payment (SOP) Act is to help companies solve such problems in a fast and efficient way. However it is very important to fully understand the Act so that companies can benefit from it to the fullest extent. This report will focus on the one of the fundamental issues frequently encountered and how lack of understanding of the Act can be critical during the legal process. The focused case study will be analyzed and discussed in details with frequent references to relevant books and articles. Moreover, precedent cases will be discussed and compared to the main case studies in this report. Lastly, a consolidated conclusions and recommendations will be presented at the end of the report.